Approaches to closure of very large atrial septal defects in older adults: Challenges, complexities, and technical strategies - Akbar, Akita Rukmana; Yogibuana, Valerinna (Heart Science Journal, 2025)
BACKGROUND: In adults, atrial septal defects (ASDs) may reach very large sizes (>40 mm), creating significant procedural challenges requiring precise imaging, including the combined use of transesophageal echocardiography (TEE) and fluoroscopy for real-time guidance during device deployment, specialized closure techniques, and close post-procedure follow-up. Adult ASD patients face hemodynamic impacts that necessitate lesion and chamber pressure measurements before closure, techniques like push-and-pull. Post-closure, antiplatelet therapy is essential to prevent thromboembolic complications. CASE: A 53-year-old woman experienced recurrent palpitations and forceful heartbeats, especially during emotional stress. Initially dismissed as normal, she later sought medical attention due to worsening shortness of breath. A pulmonologist found no lung abnormalities and referred her to a cardiologist. Transthoracic echocardiography (TTE) identified a secundum ASD with a left-to-right shunt, prompting transesophageal echocardiography (TEE) for detailed evaluation. TEE revealed a very large ASD (28–40 mm) with deficient rims: no aortic rim, minimal posterior rim, mitral rim 11 mm, IVC rim 10 mm, and SVC rim 7 mm. Transcatheter closure was guided by both fluoroscopy and transesophageal echocardiography (TEE) via left upper pulmonary vein (LUPV) approach. Fluoroscopy played a crucial role in visualizing catheter and device trajectory, ensuring precise deployment despite deficient septal rims. Transcatheter closure was planned using a 44 mm Amplatzer Septal Occluder (ASO) without any complications. CONCLUSION: Transcatheter closure is preferred for most secundum ASDs, but large defects with deficient rims increase procedural complexity and complication risks. Adequate rim evaluation is vital for device anchoring. While ASDs >38 mm or with deficient rims carry higher risks and sometimes warrant surgery, advancements in device technology allow successful percutaneous closure with careful planning. The case highlighted the critical role of TEE and fluoroscopy in accurate sizing, rim assessment, and real-time guidance, ensuring proper device selection, positioning, and minimizing complications.